Penerapan Environmental Management Accounting (EMA) Terhadap Kinerja Perusahaan - Ingrid lanita; Dyna Rachmawati (Universitas Trunojoyo Madura, 2020)
EMA is a development of management accounting, so the application of EMA is determined by contingent factors in the company. Contingency factor used in this study is business strategy. Business strategy that has been studied by previous studies is environmental strategy. However, not many previous studies have used business strategy typology (prospector or defender) as a contingent factor in the application of EMA. Several previous studies using strategy typology have proven that prospector strategies have a positive effect on the adoption of EMA. In the context of contingencies, the alignment between business strategy and EMA implementation will be able to improve business performance. This underlies the development of this research model. The alignment of the business strategy with the adoption of EMA is tested by an interaction approach. The interaction approach uses a moderated regression analysis (MRA) analysis tool. The results of testing of 348 company years (publicly listed companies that participated in PROPER during the period of 2013-2018) show that strategy had no role in strengthening or weakening the association of EMA on company performance. In other words, whatever type of strategy the company has chosen has no influence on the EMA on company performance. Testing of control variables proves that the environmental performance of the previous period did not affect the company's performance. While the size of the company and the earnings of previous period have a positive effect on performance.